Mathematics teaching materials of set integrated with Islamic values - N Nihayati; Siti Khoiriyah; N Nurmitasari; Rahmatika Kayyis (International Journal of Trends in Mathematics Education Research, 2022)
This study is a research and development (RD) to compile and develop teaching materials for mathematics an integrated set of Islamic values. The development of teaching materials is motivated by the low learning outcomes of students at the set with one cause, namely the behavior or morals of students in learning and outside learning is not good. The subjects of the study were VII grade students of SMP Muhammadiyah 1 Ambarawa. The research method is development research by adopting the Thiagarajan steps which are known as the 4D development model, namely: Define, Design, Develop and Disseminate. The results of the validation from the experts show that the feasibility level of teaching materials is in the quite feasible category or can be used but it needs to be revised slightly, with the percentage acquisition for material experts at mathematics 84.52%, material experts at Islamic values 80%, experts learning media 77.86%. The results of student responses showed that students gave a positive response to the teaching materials shown by the percentage of acquisition of responses that strongly agreed with the mathematics learning module on the interest indicator 61.59%, material indicator 53.91%, and language indicator 68.11%. In conclusion, the integrated set of mathematics teaching materials of Islamic values is feasible to use with an average percentage of validation results of 80.79% and an average percentage of student positive response results of 61.20%.